Phytoplankton Fluctuatuations under the Stress of Abiotic Factors at Kohargaddi Dam, Balrampur, India - Tewari*, B. B. Mishra, G. B. Chaturvedi, and D.D. (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> ABSTRACT: In this investigation, water samples were collected in different seasons such as rainy, winter and summer from Kohargaddi dam. Then phytoplankton diversity was studied in relation to same physico-chemical parameters. Total 18 species of phytoplankton were identified belonging Cyanophyceae, Chlorophyceae, Bacillariophyceae and Euglenophyceae. Cyanophyceae includes Nostoc sp., Oscillatoria sp., Anabaena sp., Microcystic sp., Gleocapsa sp., Spirulina sp., while Chlorophyceae includes Ulothrix sp., Chlorella sp., Spirogyra sp., Hydrodictyon sp., Pediastrum sp., Besides these, Bacillariophyceae includes Cyclotella sp., Navicula sp., Diatom sp., Synedra ulna and Euglenophyceae includes Euglena sp., Trachelomonas sp., Volvocinia sp. During phytoplankton analysis, Chlorophyceae group contributed maximum phytoplankton density followed by Cyanophyceae, Bacillariophyceae, Euglenophyceae respectively. The study reveals that plankton population is dependent upon quality of water and climatic factors. Key words: Physico-chemical parameters, Water quality, Phytoplanktons, Kohargaddi dam Environmental Biology lab. Department of Botany, M.L.K.(P.G.) College. Balrampur-271201 Please Cite This Article As: Mishra, B. B. Chaturvedi, G. B. and Tewari, D. D. 2010. Phytoplankton Fluctuatuations under the Stress of Abiotic Factors at Kohargaddi Dam, Balrampur. J. Exp. Sci. 1(5):22-24.